EMPLOYEES’ BENEFITS AND ORGANISATIONAL PERFORMANCE IN JULIUS BERGER NIGERIAN PLC - Nancy Chukwuma, Nnenna (African Journal of Social and Behavioural Sciences, 2024)
This study examines the relationship between employee benefits and organizational performance in construction companies, with a particular focus on Julius Berger Nigeria Plc, one of the leading construction firms in Nigeria. This study adopted descriptive survey design, which is concerned with determining the frequency with which something occurs or the relationships between variables. The total population is 324 permanent staff members at the head office and site supervisors. The researcher targeted 40% of the entire population, which included 130 employees. A purposive sampling of the targeted population was employed. The study used questionnaires to collect the data and consulted secondary sources and literature for comparison. This study adopted the multiple regression analysis technique to analyse the data. The results of the study revealed that training and development, as well as health and safety benefits, have positive and significant effects on organizational productivity, whereas retirement-related benefits have an insignificant negative effect on organizational productivity. Based on these findings, the study concluded that employee benefits are an important strategy for motivating staff to improve performance. The study suggests that organizations should continue providing health and security benefits to all employees, as these benefits positively influence employee performance and increase overall productivity in the company.